Peran Ulama dalam proses Rekonsiliasi Pasca Konflik di Aceh: The Roles of Ulama in the process of Post-Conflict Reconciliation in Aceh - Muhammad Sahlan; Suci Fajarni; Siti Ikramatoun; Ade Ikhsan Kamil; Iromi Ilham (Society, 2019)
In the context of Aceh, the word “Ulama" refers to an Islamic scholar who own boarding school (In Aceh language known as Dayah) or a leader of an Islamic boarding school (known as Teungku Dayah). Ulama become "the backbone" of any social problem and play strategic and influential roles in Acehnese society. However, The Ulama roles have changed in the post-conflict era in Aceh. The assumption that Ulama are unable running their authorities in Acehnese society especially in the post-conflict era. Ideally, their roles are needed in the reconciliation regarding the agents of reconciliation who have authority like the Ulama and are trustworthy by Acehnese society. Therefore, this article aims to discuss the position of Ulama in the process of post-conflict reconciliation in Aceh. To investigate the problem, a descriptive qualitative method was used, where the method is to describe the nature of a temporary situation that occurs when the research is carried out in detail, and then the causes of the symptoms were examined. The data were literature studies, participatory observation, and in-depth interviews. The results of this research showed that during an important period of Aceh's history, the Ulama constantly become guardians that provide a religious ethical foundation for each socio-political change in Aceh, and subsequently they also act as the successor to the religious style that developed in the society. Even the formation and development of the socio-political and cultural system occurred partly on the contribution of the Ulama. The position of Ulama in the process of post-conflict reconciliation in Aceh can be found in four ways. Firstly, knowledge transmission. Secondly, as a legal decision-maker which refers to Sharia law, especially related to the reconciliation process. Thirdly, as a mediator. Fourthly, cultural roles in the form of ritual or ceremonial guides that are carried out when the parties of the conflict have met an agreement to reconcile.